The Study Effect Of Curcumin On Some Of Chemophysiological Parameters And Spinal Cord Tissue In Male Rabbits Subjected To Monosodium Glutamate - Alsalame, Heba A. Abd-Alsalam; Al-Bazii, Wefak G. Mohammad; Al-Habeb, May May F. Magid (Journal of Kerbala for Agricultural Sciences, 2017)
This study aimed to know the preventive role of a substance Curcumin . against damage happening in the nervous system and induced textured monosodium glutamate (MSG) in male rabbits. , sixty of adult male rabbits were randomly divided into four equal groups (15 animals / group), the first group (G1) intubated with 1 ml / kg ml / kg of corn oil and served as a control group (G1) . The second group were intubated orally and daily with 3mg /kg of MSG for three months , while the third group (G3) has intubated orally and daily with 60 mg / kg curcumin for three months, the fourth group intubated orally and daily with 3mg /kg of MSG and 60 mg / kg of curcumin for three months .Fasting blood samples were collected from fasted rabbits at pretreated period , Mid-experiment and at the end of experiment to study the following parameters : concentration of Total protein (TP) and Glucose (GLU) in cerebeospinal fluid . The results revealed that oral dosing with MSG caused a significant decrease (P <0.01)in concentration of TP and significant increase (P <0.01) in concentration of GLU compared with the control group. The group that treated with 60mg / kg curcumin revealed a significant increase (P <0.01) in concentration of TP while no significant difference was observed in the concentration of GLU compared with the control group. Experience also shows that oral dosing with MSG and curcumin caused significant decrease (P <0.01) in the concentration TP , and significant increase in the concentration of GLU after end of three months compared with the control group . Histological results from rabbits treated with MSG for three months have showed degenerative changes in spinal cord after staining with H&E , the treatment of nervous tissue with Silver stain showed deposit of beta Amleod Aβ plaques in spinal cord compared with the control group while the results showed the natural structure of spinal cord by H&E and Silver stain after treatment with curcumin, but for the group that treated with MSG and curcumin has been observed the natural appearance of the nervous tissue with little appearance of some of the gaps by H & E with lack of deposition of Aβ in the spinal cord by Silver stain compared with the control group. In conclusion , results of this study that monosodium glutamate (MSG) causes clearly pathological changes in nervous tissue and confirm the protective role of Curcumin against the pernicious influence of the nervous tissue and Some of the ions in the serum of male rabbit